Sheltie and the runaway - Clover, Peter (New York : Aladdin Paperbacks, 2000)
When a family with a girl her age moves into nearby Fox Hall Manor, Emma hopes to make a new friend, but the girl's overprotective father blames Emma and her pony when his daughter runs away.
"Activity fun pages inside"--Cover.
Ages 6-8.
Keywords: Shetland pony -- Juvenile fiction; Ponies -- Juvenile fiction; Runaway children -- Juvenile fiction; Fathers and daughters -- Juvenile fiction